Have sanctions modified Iran's trade policy? An evidence of asianization and de-europeanization through the gravity model - Liudmila Popova; Ehsan Rasoulinezhad (Economies, 2016)
This study is an empirical attempt to find out whether under sanctions Iran's trade direction has shifted away from Europe (trade policy of de-Europeanization) towards Asia (trade policy of Asianization). The analysis is conducted using a panel-gravity trade model to analyze bilateral trade pattern between Iran and 50 countries from the EU and Asia during the period 2006-2013. To this end, the authors use an extended gravity model by adding new variables, including the index of Chinn-Ito (KAOPEN) as an indicator of financial openness, and the composite trade intensity (CTI) as an indicator of trade openness. Our findings reveal that the gravity equation fits the data reasonably well. The empirical evidence indicates a significant negative effect of sanctions on Iran-EU bilateral trade (by an average of 46.9%), while it has a positive impact on trade between Iran and the Asian countries (by an average of 85.2%). Overall, these findings confirm that the imposition of various sanctions related to Iran's nuclear program has pushed the country's foreign trade to reorient away from Europe towards Asia.
Keywords: C33; F10; 330; sanctions; trade policy; gravity model; Iran